Regulation fair disclosure and the market’s reaction to analyst investment recommendation changes - Cornett, Marcia Millon; Tehranian, Hassan; Yalçın, Atakan (Journal of Banking & Finance, 2007)
Previous research has shown that affiliated analysts (those who are working for investment banks that underwrite securities for companies) have an incentive to provide optimistically biased recommendations from selective information they are given by the firm. In an effort to halt such activities, as of October 2000, Regulation Fair Disclosure (RegFD) prohibits selective disclosure of material non-public information by public companies to privileged individuals (such as favored research analysts) and requires broad, non-exclusionary disclosure of such information. We examine firms’ stock price reactions to investment recommendation changes from affiliated analysts versus unaffiliated analysts from October 1998 to November 2002, around the passage of RegFD. Similar to previous research, we find that investors reacted more significantly to recommendation downgrades by affiliated analysts than to those by unaffiliated analysts prior to the passage of RegFD. However, we find that the difference in the reactions to recommendation changes is not present after the passage of RegFD. We also find that stock price reactions to analysts’ (both affiliated and unaffiliated) recommendation changes decreased significantly after the passage of RegFD. Thus, RegFD appears to have curbed the selective disclosure of information (particularly negative information) by firms to affiliated analysts. Further, the smaller reactions to recommendation changes by all analysts after RegFD may reflect a change in analysts’ behavior (irrespective of information that is available) or a response by corporate managers to withhold information rather than risking a violation of fair disclosure rules.